David against Goliath: How creative communication helps small advertising agencies survive in a market led by giant agencies - Jenny-Maria Åström; Karim Carroum Sanz; Sofia Lena Hagström; Andreu Safont Bagué; Jo\~ao Pedro Teles Estima (International Journal of Business and Economic Sciences Applied Research (IJBESAR), 2017)
Purpose: The purpose of the study is to research how national advertising agencies use creativity to compete with larger, global agencies in the advertising market of Sweden, Spain and Portugal. Design/methodology/approach: To conduct the study, the authors keep a qualitative approach: we first carry out an analysis of previous studies about creativity, communication and entrepreneurial orientation, followed by interviews with one small and one large advertising agency for each country. Findings: The findings of the study show that smaller agencies have higher levels of competitive aggressiveness and risk-taking, because of the wish to expand and vulnerability to their larger clients. The levels of opportunity recognition are higher in the large agencies because of their resource assets. All agencies are creative and innovative and equally as proactive, but because the speed of the decision-making process can be faster and communication skills better in a small agency, they can reach higher levels of proactiveness Research limitations/implications: The implications of the study show that the entrepreneurial orientation to some extent can be used by small agencies to gain competitive advantages on the advertising market. Originality/value: To the best of our knowledge there is no similar study available. This study showed that entrepreneurial orientation, to some extent, can be used by small agencies to gain competitive advantages in the advertising market.
Keywords: M37; M1; 330; Creativity; Communication; Advertising; Entrepreneurship; Entrepreneurial Orientation